A Qualitative Study to Explore Patients', Carers' and Health Professionals' Views to Culturally Adapt CBT for Psychosis (CBTp) in Pakistan. Issue 1 (2nd September 2014) - Naeem, Farooq; Habib, Nazish; Gul, Mirrat; Khalid, Mehwish; Saeed, Sofiya; Farooq, Saeed; Munshi, Tariq; Gobbi, Mary; Husain, Nusrat; Ayub, Muhammad; Kingdon, David
Abstract : Background: Cognitive Behaviour Therapy (CBT) has an established evidence base and is recommended by the national organizations in United Kingdom and the United States. CBT remains under utilized in low and middle income countries. CBT was developed in the west and it has been suggested that it is underpinned by western values. It therefore follows that to make CBT accessible for non western clients, it needs adapting into a given culture.Aims: Our aim was to develop guidelines for adapting CBT for psychosis in Pakistan by incorporating the views of the patients, their carers and mental health professionals.Method: We conducted a series of qualitative studies in Pakistan to adapt CBT for psychosis (a total of 92 interviews). The data were analyzed by systematic content and question analysis. Analysis started by identifying emerging themes and categories. Themes emerging from the analyses of interviews by each interviewer were compared and contrasted with others interviewers constantly. Triangulation of themes and concepts was undertaken to further compare and contrast the data from the different participating groups.Results: The results of these studies highlighted the barriers in therapy as well as strengths while working with this patient group. Patients and their carers in Pakistan use a bio-psycho-spiritual-social model of illness. They seek help from various sources. Therapists make minor adjustments in therapy.Conclusions: The findings from this study will help therapists working with this client group using CBT for psychosis in Pakistan. These results need to be tested through controlled trials.